ModelMatcher: A scientist‐centric online platform to facilitate collaborations between stakeholders of rare and undiagnosed disease research. Issue 6 (24th March 2022) - Harnish, J. Michael; Li, Lucian; Rogic, Sanja; Poirier‐Morency, Guillaume; Kim, Seon‐Young; ,; Boycott, Kym M.; Wangler, Michael F.; Bellen, Hugo J.; Hieter, Philip; Pavlidis, Paul; Liu, Zhandong; et al.
Abstract: Next‐generation sequencing is a prevalent diagnostic tool for undiagnosed diseases and has played a significant role in rare disease gene discovery. Although this technology resolves some cases, others are given a list of possibly damaging genetic variants necessitating functional studies. Productive collaborations between scientists, clinicians, and patients (affected individuals) can help resolve such medical mysteries and provide insights into in vivo function of human genes. Furthermore, facilitating interactions between scientists and research funders, including nonprofit organizations or commercial entities, can dramatically reduce the time to translate discoveries from bench to bedside. Several systems designed to connect clinicians and researchers with a shared gene of interest have been successful. However, these platforms exclude some stakeholders based on their role or geography. Here we describe ModelMatcher, a global online matchmaking tool designed to facilitate cross‐disciplinary collaborations, especially between scientists and other stakeholders of rare and undiagnosed disease research. ModelMatcher is integrated into the Rare Diseases Models and Mechanisms Network and Matchmaker Exchange, allowing users to identify potential collaborators in other registries. This living database decreases the time from when a scientist or clinician is making discoveries regarding their genes of interest, to when they identify collaborators and sponsors to facilitate translational and therapeutic research. Abstract : ModelMatcher is a matchmaking website that connects various stakeholders of rare and undiagnosed research to scientists with specific expertise and interests. This platform is connected with large clinical and scientific registries through Matchmaker Exchange and Rare Diseases Models and Mechanisms Networks, respectively, facilitating cross‐disciplinary collaborations on a global scale.